A method for deep detoxification of secondary aluminum ash by wet method

Through the synergistic action of mechanical activation and chemical reaction, combined with dry ball mill and wet ball mill, and the use of specific additives and inducers, the problems of low detoxification efficiency and pollution of aluminum ash slag are solved, and the efficient and harmless utilization of aluminum ash slag and the acquisition of high-quality aluminum raw materials are achieved.

CN115739915BActive Publication Date: 2025-04-11CENT SOUTH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211171851.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-26
Publication Date
2025-04-11
Estimated Expiration
2042-09-26

AI Technical Summary

Technical Problem

The existing detoxification methods of aluminum ash slag have problems such as denitrification, low efficiency of desalination, desalination and fluorine fixation, complex process, and emission of polluted waste, making it difficult to achieve efficient and harmless utilization of aluminum ash slag.

Method used

Mechanical activation and chemical reactions are used to promote the deep removal of poisoned elements in aluminum ash slag. Through the combination of dry ball milling and wet ball milling, ball milling additives such as calcium chloride and calcium peroxide and reaction inducers such as ammonium bicarbonate and calcium lignin sulfonate are used to achieve efficient nitrogen removal, desalting and fluorine-fixed aluminum ash slag.

Benefits of technology

It has achieved deep detoxification of aluminum ash slag, obtained high-quality aluminum raw materials, and has no pollution-free waste emissions in the process, is simple to operate, has low cost, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115739915B_ABST
    Figure CN115739915B_ABST
Patent Text Reader

Abstract

The invention discloses a method for deep detoxification of secondary aluminum ash by wet method, which comprises dry ball milling aluminum ash slag and ball milling aid (including calcium chloride and calcium peroxide), wet ball milling the dry ball milled material and reaction inducer (including ammonium bicarbonate and calcium lignin sulfonate) and water, filtering and drying the wet ball milled material to obtain deep detoxified aluminum ash slag. The method realizes deep detoxification of aluminum ash slag under the condition of low liquid-solid ratio through the synergistic effect of mechanical activation and chemical reaction, and does not need to add other acids or alkalis; the filtrate generated in the process is directly returned to the wet ball milling hydrolysis process as a hydrolyzate for recycling, and there is no wastewater or waste discharge in the whole process, and the technical route is simple to operate, low in cost, and easy to realize industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for treating aluminum ash slag, in particular to a method for secondary aluminum ash wet deep detoxification, and belongs to the technical field of harmless treatment of aluminum ash slag solid waste. Background Art

[0002] Aluminum slag is a hazardous solid waste generated during the production, processing and recycling of the aluminum industry. It is produced during the melting of all aluminum. During the melting of metal aluminum, the surface aluminum liquid is oxidized into Al2O3 and AlN after contact with air, and then separated and collected by slag removal after cooling. With the rapid development of the aluminum industry and the increasing proportion of recycled aluminum year by year, the output of aluminum slag has also increased sharply. According to incomplete statistics, the annual output of aluminum slag in China has reached more than 3 million tons, but its comprehensive utilization rate is less than 30%. Most of the aluminum slag is stored, and the cumulative stockpile volume exceeds 10 million tons.

[0003] Aluminum ash slag will release a gas with a pungent odor during the storage process. This is because AlN is very active and reacts with water in the air to produce ammonia, which not only corrodes equipment but also affects human health. Salt substances such as Na, K, F, and Cl will cause water pollution and soil salinization during the storage process, which will cause great harm to corporate production and the ecological environment. At the same time, aluminum ash slag contains a large amount of valuable elements, among which the aluminum content is more than 40%, which is much higher than the aluminum content in bauxite, and has great utilization value. The important factor restricting the recycling of aluminum ash slag is the presence of active components AlN and poisonous components such as Na, K, F, and Cl.

[0004] At present, there are some related technologies for the detoxification of aluminum ash. Chinese patent CN 108671462 A discloses a method for denitrification of aluminum ash, which is specifically performed by adding aluminum ash and hydrogen peroxide, peracetic acid, dilute sulfuric acid and other reactants into water for stirring, and then obtaining the denitrified aluminum ash by multi-stage filtration. This method can well inhibit the release of ammonia during hydrolysis, but the liquid-solid ratio of the reaction is relatively high, reaching a maximum of 10. After denitrification, a lot of wastewater is produced with complex components, which is difficult to handle. Chinese patent CN10927654B discloses a low-pollution secondary aluminum ash treatment method. This method adopts water washing desalination, liquid-solid separation filtrate defluorination, filtrate evaporation crystallization recovery of composite salt, liquid-solid separation filter cake roasting denitrification, and realizes the harmless utilization of secondary aluminum ash. However, this method has a long process, which is not conducive to industrial production, and the intermediate product may have secondary pollution. Summary of the invention

[0005] In view of the technical problems existing in the aluminum ash detoxification process disclosed in the above-mentioned prior art, the purpose of the present invention is to provide a method for synergistically promoting the deep removal of poisonous elements in aluminum ash based on mechanical activation and chemical reaction. The method can simultaneously achieve efficient denitrification, desalination and fluorine fixation of aluminum ash, and obtain high-quality aluminum raw materials, which can be widely used as raw materials for producing calcium aluminate steelmaking desulfurization agent, heat storage balls, refractory materials, Silon composite materials, etc., and the method has no pollution waste discharge in the whole process, and the technical route is simple to operate, low cost, and easy to realize industrial production.

[0006] In order to achieve the above technical objectives, the present invention provides a method for deep detoxification of secondary aluminum ash by wet method, which comprises dry ball milling aluminum ash slag and a ball milling aid, wet ball milling the dry ball milled material with a reaction inducer and water, and filtering and drying the wet ball milled material; the ball milling aid comprises calcium chloride and calcium peroxide; the reaction inducer comprises ammonium bicarbonate and calcium lignin sulfonate.

[0007] The technical solution of the present invention aims to use mechanical activation and chemical reaction to achieve efficient denitrification, desalination and fluorine fixation of aluminum ash slag at the same time, so as to achieve the purpose of deep detoxification of aluminum ash slag and obtain high-quality aluminum raw materials. First of all, dry ball milling can fully dissociate the mineral phase in the aluminum ash slag, so that aluminum nitride and the like are fully exposed, and the specific surface area of ​​the aluminum ash slag can be greatly increased, and its reaction activation energy can be reduced, which is beneficial to the subsequent chemical hydrolysis process. However, during the dry ball milling process, the aluminum nitride phase in the aluminum ash slag is constantly exposed, and it is easy to react with moisture in the air to produce harmful ammonia. By adding grinding aids including calcium chloride and calcium peroxide components, moisture in the air can be absorbed during the dry ball milling process, thereby inhibiting the generation of ammonia and reducing corrosion to the equipment. At the same time, calcium salts can react with F in the aluminum ash slag during the subsequent wet milling process. - Combine to make F - It is solidified in the aluminum ash slag in the form of CaF2, and the introduction of calcium salt can further promote the removal of NaCl and KCl during wet ball milling. Secondly, the material separated by dry ball milling is detoxified by hydrolysis reaction. During the hydrolysis of aluminum ash slag, AlN phase will generate Al(OH)3 on the surface during the reaction process, and calcium salt and F will be generated at the same time. -The generated calcium fluoride will also be adsorbed and deposited on the surface of aluminum ash slag, making it difficult for the internal AlN to directly contact and react with water, hindering the further occurrence of the reaction. By using ball milling to assist hydrolysis and using an inducer containing ammonium bicarbonate and calcium lignin sulfonate to promote the hydrolysis reaction, ammonium bicarbonate mainly provides an initial weak alkaline environment for the hydrolysis reaction, which can promote the hydrolysis reaction. Under the action of mechanical ball milling, the surface layer of aluminum ash slag can be continuously peeled off, so that the AlN inside the particles is gradually exposed, and then directly contacted and reacted with water. Calcium lignin sulfonate can be adsorbed on the surface of aluminum ash slag particles, balancing the excess valence bonds on the surface of the particles, so that the cohesion between the particles is shielded, avoiding the agglomeration of the particles, and at the same time significantly reducing the surface free energy of the aluminum ash slag particles, increasing the fragility of the particles, and further promoting the refinement of the aluminum ash slag particles, thereby accelerating the hydrolysis reaction.

[0008] As a preferred solution, the mass ratio of calcium chloride to calcium peroxide in the ball milling aid is 1:0.3-0.8. During dry grinding, the calcium chloride and calcium peroxide compound exhibits strong hygroscopicity, which can effectively inhibit the release of ammonia by the reaction of moisture in the air with aluminum nitride during dry grinding, while in the wet grinding process, calcium chloride mainly releases calcium ions. The presence of a large amount of calcium ions can promote the dissolution of Na and K, and can solidify fluoride ions at the same time. Calcium peroxide reacts with water to form calcium hydroxide, which can provide an alkaline environment for the removal of nitrogen. Maintaining calcium chloride and calcium peroxide within an appropriate ratio is beneficial for inhibiting the release of ammonia during dry grinding and promoting the removal of nitrogen and salts during wet grinding.

[0009] As a preferred solution, the ball milling aid contains sodium peroxide; the mass ratio of the sodium peroxide to calcium chloride is not greater than 0.5. Sodium peroxide is also a deliquescent compound. Adding an appropriate amount of sodium peroxide can cooperate with calcium chloride and calcium peroxide to inhibit the generation of ammonia during dry grinding. At the same time, sodium peroxide and calcium peroxide show alkalinity during wet grinding, which can cooperate with the reaction inducer to promote the reaction of aluminum nitride and water, thereby promoting the removal of nitrogen. However, too much sodium peroxide will introduce too much Na, which is not conducive to the removal of Na salts.

[0010] As a preferred solution, the mass of the ball milling aid is 1% to 6% of the mass of the aluminum ash slag. If the amount of ball milling aid added is too low, ammonia gas is easily generated during the dry ball milling process, which is disadvantageous. Too much ball milling aid will increase the ball milling load and reduce production efficiency.

[0011] As a preferred solution, the particle size distribution of the dry ball milled material satisfies: -800 mesh particle size accounts for 40% to 60% by mass, -400 mesh particle size accounts for 60% to 80% by mass, and -200 mesh particle size accounts for not less than 90% by mass. The particle size of aluminum ash slag will affect the removal rate of poisonous elements in secondary aluminum ash. By ball milling to an appropriate particle size, the AlN and other phases inside the aluminum ash slag particles are fully exposed, thereby promoting the removal rate of nitrogen during the hydrolysis reaction.

[0012] As a preferred solution, the mass ratio of ammonium bicarbonate to calcium lignin sulfonate in the reaction inducer is 1:1-5. As a buffer weak base component, ammonium bicarbonate can stabilize the weak alkaline environment of the system during wet grinding, which is conducive to promoting the hydrolysis process of aluminum nitride, while calcium lignin sulfonate can be adsorbed on the surface of aluminum ash particles, balancing the excess valence bonds on the surface of the particles, thereby shielding the cohesion between the particles and avoiding the agglomeration of the particles. At the same time, it can significantly reduce the surface free energy of the aluminum ash particles, improve the fragility of the particles, and further promote the refinement of the aluminum ash particles, thereby accelerating the hydrolysis reaction. Adding too high a proportion of lignin sulfonate is not conducive to the subsequent use of aluminum ash.

[0013] As a preferred solution, the reaction inducer contains polyethylene glycol; the mass ratio of the polyethylene glycol to ammonium bicarbonate is not greater than 3. Polyethylene glycol has good hydrophilicity. When introduced into the wet ball milling process, it can not only cooperate with calcium lignin sulfonate to act as a surfactant to further promote the dispersibility of aluminum ash slag particles, but also improve the wettability of the aluminum ash slag surface, promote the full contact between aluminum ash slag particles and water, and improve the removal efficiency of AlN. Preferred polyethylene glycols include polyethylene glycol 2000, polyethylene glycol 3000, polyethylene glycol 4000, and the like.

[0014] As a preferred solution, the mass of the reaction inducer is 0.5% to 2% of the mass of the aluminum ash slag.

[0015] As a preferred solution, the liquid-to-solid ratio of water to aluminum ash slag is 0.5-3 mL:1 g.

[0016] As a preferred solution, the conditions of wet ball milling are: temperature of 50-100°C, time of 1-5h, ball milling speed of 50-150r / min, ball milling medium volume filling rate of 35%-50%, ball milling medium ratio of 8mm diameter zirconium ball mass proportion of 25%-35%, diameter of 10mm zirconium ball mass proportion of 30%-50%, diameter of 12mm zirconium ball mass proportion of 25%-35%. The present invention adopts ball milling to assist the hydrolysis reaction process, and the oxidation layer outside the aluminum ash slag particles can be destroyed by mechanical ball milling, and Al(OH)3 generated by hydrolysis of the outer layer in an alkaline environment will continuously dissolve into the solution in the form of metaaluminate, which is conducive to exposing new reaction interfaces, and mechanical energy can be used to activate AlN particles, reduce their reaction activation energy, and promote hydrolysis reaction. Therefore, through the synergistic effect of mechanical activation and chemical reaction of ball milling, the rapid removal of N in aluminum ash slag is achieved. Based on the slow kinetic reaction of Al(OH)3 dissolution, appropriately increasing the temperature can further promote the dissolution of Al(OH)3 and thus accelerate the hydrolysis of AlN.

[0017] As a preferred solution, the filtrate produced by the filtration is returned to the wet ball milling process.

[0018] As a preferred solution, the aluminum ash slag has a metal aluminum content of 1% to 10%, an Al2O3 content of 20% to 60%, an AlN content of 2% to 30%, a fluorine content of 0.5% to 5%, and a total content of NaCl and KCl of 3% to 20%.

[0019] Compared with the prior art, the technical solution of the present invention brings the following beneficial technical effects:

[0020] 1) The present invention uses a low liquid-solid ratio to achieve deep detoxification of secondary aluminum ash, and the generated filtrate can be returned to the wet ball milling hydrolysis process as a hydrolyzate, avoiding the discharge of wastewater and being environmentally friendly.

[0021] 2) The present invention combines dry ball milling and wet ball milling hydrolysis processes to achieve rapid removal of nitrogen, NaCl and KCl in aluminum ash and solidification of F through the synergistic effect of physical grinding mechanical activation and chemical reaction.

[0022] 3) The present invention further strengthens the mechanical activation effect of ball milling by adding ball milling aids and reaction inducers, and accelerates the removal and solidification reaction of poisonous elements, thereby achieving simultaneous denitrification, defluorination and desalination of secondary aluminum ash without the need to add other acids or alkalis. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0024] The following examples are intended to further illustrate the present invention, rather than to limit the scope of protection of the claims of the present invention.

[0025] Comparative Example 1

[0026] Aluminum ash slag wet ball milling process uses high liquid-to-solid ratio for hydrolysis.

[0027] Aluminum ash (metal aluminum content 8.9%, Al2O3 content 44.9%, AlN content 20.5%, NaCl / KCl total content 6.1%, fluorine content 2.56%) produced by a recycled aluminum plant was used as raw material; firstly, the aluminum ash slag was added with 3% ball milling aid (calcium chloride: calcium peroxide: sodium peroxide = 1:0.5:0.5) for dry ball milling. After ball milling, the mass of the -800 mesh size of the material accounted for 50.3%, the -400 mesh size accounted for 69.6%, and the -200 mesh size accounted for 91.8%; the obtained ball milled material was added with ammonium bicarbonate: lignin sulfonic acid A solid mixture of calcium: polyethylene glycol (PEG4000) = 1:3:2, water is added at the same time for ball milling hydrolysis, the volume ratio of aluminum ash slag mass to water in the wet ball milling hydrolysis process is controlled to be 1:10g / ml, and the amount of the solid mixture added is 1.5% of the mass of aluminum ash slag; the wet ball milling speed is 100r / min, the medium filling rate is 40%, the medium ratio is: the mass of zirconium balls with a diameter of 8mm accounts for 30%, the mass of zirconium balls with a diameter of 10mm accounts for 40%, and the mass of zirconium balls with a diameter of 12mm accounts for 30%, the ball milling hydrolysis temperature is 50°C, and the ball milling hydrolysis time is 3h. After wet ball milling hydrolysis, the material is filtered and dried to obtain the detoxified aluminum ash slag. After testing, the nitrogen removal rate is 57.46%, the salt removal rate is 93.41%, and the fluorine solidification rate is 96.48%.

[0028] Comparative Example 2

[0029] No grinding aid is added during the dry ball milling process of aluminum ash slag.

[0030] Aluminum ash (metal aluminum content 8.9%, Al2O3 content 44.9%, AlN content 20.5%, NaCl / KCl total content 6.1%, fluorine content 2.56%) produced by a recycled aluminum plant was used as raw material; firstly, the aluminum ash slag was dry-milled, and the mass of the material after ball milling was 50.1% in the -800 mesh size, 71.6% in the -400 mesh size, and 90.2% in the -200 mesh size; the obtained ball-milled material was mixed with ammonium bicarbonate: calcium lignin sulfonate: polyethylene glycol (PEG4000) = 1 :3:2 solid mixture, water is added for ball milling hydrolysis, the volume ratio of aluminum ash slag mass to water in the wet ball milling hydrolysis process is controlled to be 1:1.5g / ml, and the amount of the solid mixture added is 1.5% of the mass of aluminum ash slag; the wet ball milling speed is 100r / min, the medium filling rate is 40%, the medium ratio is: the mass of zirconium balls with a diameter of 8mm accounts for 30%, the mass of zirconium balls with a diameter of 10mm accounts for 40%, and the mass of zirconium balls with a diameter of 12mm accounts for 30%, the ball milling hydrolysis temperature is 50°C, and the ball milling hydrolysis time is 3h. After wet ball milling hydrolysis, the material is filtered and dried to obtain the detoxified aluminum ash slag. After testing, the nitrogen removal rate is 74.66%, the salt removal rate is 89.39%, and the fluorine solidification rate is 49.37%.

[0031] Comparative Example 3

[0032] No reaction inducer is added during the wet ball milling process of aluminum ash slag.

[0033] Aluminum ash (metal aluminum content 8.9%, Al2O3 content 44.9%, AlN content 20.5%, NaCl / KCl total content 6.1%, fluorine content 2.56%) produced by a recycled aluminum plant was used as raw material; firstly, the aluminum ash slag was added with 3% ball milling aid (calcium chloride: calcium peroxide: sodium peroxide = 1:0.5:0.5) for dry ball milling. After ball milling, the mass of the material with -800 mesh size accounted for 52.4%, the mass of -400 mesh size accounted for 71.1%, and the mass of - 200 particle size accounts for 93.7%; add water to the obtained ball mill material for ball milling hydrolysis, and control the volume ratio of aluminum ash slag mass to water in the wet ball milling hydrolysis process to be 1:1.5g / ml; the wet ball milling speed is 100r / min, the medium filling rate is 40%, the medium ratio is: 8mm diameter zirconium ball mass accounts for 30%, 10mm diameter zirconium ball mass accounts for 40%, and 12mm diameter zirconium ball mass accounts for 30%, the ball milling hydrolysis temperature is 50℃, and the ball milling hydrolysis time is 3h. After wet ball milling hydrolysis, the material is filtered and dried to obtain the detoxified aluminum ash slag. After testing, the nitrogen removal rate is 67.27%, the salt removal rate is 90.97%, and the fluorine solidification rate is 95.73%.

[0034] Comparative Example 4

[0035] Stirring is used instead of wet ball milling for hydrolysis.

[0036] Aluminum ash (metal aluminum content 8.9%, Al2O3 content 44.9%, AlN content 20.5%, NaCl / KCl total content 6.1%, fluorine content 2.56%) produced by a recycled aluminum plant was used as raw material; firstly, the aluminum ash slag was added with 3% ball milling aid (calcium chloride: calcium peroxide: sodium peroxide = 1:0.5:0.5) for dry ball milling. After ball milling, the mass of the material with -800 mesh size accounted for 49.2%, and the mass of the material with -400 mesh size accounted for 73. 5%, -200 particle size accounts for 92.4%; the obtained ball-milled material is added with a solid mixture of ammonium bicarbonate: calcium lignin sulfonate: polyethylene glycol (PEG4000) = 1:3:2, and water is added for stirring and hydrolysis, and the volume ratio of aluminum ash slag mass to water during the hydrolysis process is controlled to be 1:1.5g / ml, and the amount of the solid mixture added is 1.5% of the aluminum ash slag mass; the stirring speed is 100r / min, the hydrolysis temperature is 50°C, and the hydrolysis time is 3h. After stirring and hydrolysis, the material is filtered and dried to obtain the detoxified aluminum ash slag. After testing, the nitrogen removal rate is 68.21%, the salt removal rate is 94.97%, and the fluorine solidification rate is 93.47%.

[0037] Example 1

[0038] Aluminum ash (metal aluminum content 8.9%, Al2O3 content 44.9%, AlN content 20.5%, NaCl / KCl total content 6.1%, fluorine content 2.56%) produced by a recycled aluminum plant was used as raw material; first, the aluminum ash slag was added with 3% ball milling aid (calcium chloride: calcium peroxide: sodium peroxide = 1:0.5:0.5) for dry ball milling. After ball milling, the mass of the -800 mesh size of the material accounted for 53.6%, the -400 mesh size accounted for 74.7%, and the -200 mesh size accounted for 94.3%; the obtained ball milled material was added with ammonium bicarbonate: calcium lignin sulfonate : polyethylene glycol (PEG4000) = 1:3:2 solid mixture, water is added for ball milling hydrolysis, the volume ratio of aluminum ash slag mass to water in the wet ball milling hydrolysis process is controlled to be 1:1.5g / ml, and the amount of the solid mixture added is 1.5% of the mass of the aluminum ash slag; the wet ball milling speed is 100r / min, the medium filling rate is 40%, the medium ratio is: the mass of the zirconium ball with a diameter of 8mm accounts for 30%, the mass of the zirconium ball with a diameter of 10mm accounts for 40%, and the mass of the zirconium ball with a diameter of 12mm accounts for 30%, the ball milling hydrolysis temperature is 50°C, and the ball milling hydrolysis time is 3h. After the wet ball milling hydrolysis, the material is filtered and dried to obtain the detoxified aluminum ash slag. After testing, the main components of aluminum ash slag after wet detoxification are as follows: Total-Al content 38.06%, AlN content 0.48%, Na content 0.11%, K content 0.09%, Cl content <0.01%, F content 2.04%, Ca content 1.19%, aluminum ash slag weight gain 21.3%. The calculated nitrogen removal rate is 97.17%, the salt removal rate is 98.13%, and the fluorine solidification rate is 96.71%.

[0039] Example 2

[0040] Aluminum ash (metal aluminum content 5.2%, Al2O3 content 51.9%, AlN content 18.6%, NaCl / KCl total content 8.9%, fluorine content 3.02%) produced by a recycled aluminum plant was used as raw material; firstly, the aluminum ash slag was added with 6% ball milling aid (calcium chloride: calcium peroxide: sodium peroxide = 1:0.3:0.5) for dry ball milling. After ball milling, the mass of the -800 mesh size of the material accounted for 59.6%, the -400 mesh size accounted for 80.2%, and the -200 mesh size accounted for 96.8%; the obtained ball milled material was added with ammonium bicarbonate: lignin sulfonic acid A solid mixture of calcium: polyethylene glycol (PEG4000) = 1:1:3, water is added at the same time for ball milling hydrolysis, the volume ratio of aluminum ash slag mass to water in the wet ball milling hydrolysis process is controlled to be 1:3g / ml, and the amount of the solid mixture added is 2% of the mass of the aluminum ash slag; the wet ball milling speed is 150r / min, the medium filling rate is 40%, the medium ratio is: the mass of the zirconium ball with a diameter of 8mm accounts for 30%, the mass of the zirconium ball with a diameter of 10mm accounts for 40%, and the mass of the zirconium ball with a diameter of 12mm accounts for 30%, the ball milling hydrolysis temperature is 100℃, and the ball milling hydrolysis time is 2h. After the wet ball milling hydrolysis, the material is filtered and dried to obtain the detoxified aluminum ash slag. After testing, the nitrogen removal rate is 97.90%, the salt removal rate is 96.79%, and the fluorine solidification rate is 99.21%.

[0041] Example 3

[0042] Aluminum ash (metal aluminum content 5.2%, Al2O3 content 51.9%, AlN content 18.6%, NaCl / KCl total content 8.9%, fluorine content 3.02%) produced by a recycled aluminum plant was used as raw material; firstly, the aluminum ash slag was added with 4% ball milling aid (calcium chloride: calcium peroxide: sodium peroxide = 1:0.8:0.2) for dry ball milling. After ball milling, the mass of the material with -800 mesh size accounted for 48.1%, the mass of the -400 mesh size accounted for 69.9%, and the mass of the -200 mesh size accounted for 91.7%; the obtained ball milled material was added with bicarbonate of soda ash to obtain a slag. A solid mixture of ammonium: calcium lignin sulfonate = 1:5, water is added for ball milling hydrolysis, the volume ratio of aluminum ash slag mass to water in the wet ball milling hydrolysis process is controlled to be 1:0.5g / ml, and the amount of the solid mixture added is 0.5% of the mass of aluminum ash slag; the wet ball milling speed is 50r / min, the medium filling rate is 40%, the medium ratio is: the mass of zirconium balls with a diameter of 8mm accounts for 30%, the mass of zirconium balls with a diameter of 10mm accounts for 40%, and the mass of zirconium balls with a diameter of 12mm accounts for 30%, the ball milling hydrolysis temperature is 80°C, and the ball milling hydrolysis time is 5h. After wet ball milling hydrolysis, the material is filtered and dried to obtain the detoxified aluminum ash slag. After testing, the nitrogen removal rate is 91.36%, the salt removal rate is 95.90%, and the fluorine solidification rate is 96.33%.

[0043] Keeping the other conditions unchanged, polyethylene glycol (PEG4000) was further added during the wet ball milling process, and the mass ratio of polyethylene glycol to ammonium bicarbonate was 2.5:1. After testing, the nitrogen removal rate was increased to 97.84%, indicating that the addition of polyethylene glycol during the wet ball milling process is conducive to further improving the denitrification effect.

[0044] Example 4

[0045] Aluminum ash (metal aluminum content 8.9%, Al2O3 content 44.9%, AlN content 20.5%, NaCl / KCl total content 6.1%, fluorine content 2.56%) produced by a recycled aluminum plant was used as raw material; firstly, the aluminum ash slag was added with 1% ball milling aid (calcium chloride: calcium peroxide: sodium peroxide = 1:0.8:0.1) for dry ball milling. After ball milling, the mass of the -800 mesh size of the material accounted for 45.8%, the -400 mesh size accounted for 68.8%, and the -200 mesh size accounted for 91.5%; the obtained ball milled material was added with ammonium bicarbonate: lignin sulfonic acid A solid mixture of calcium: polyethylene glycol (PEG4000) = 1:5:1, water is added for ball milling hydrolysis, the volume ratio of aluminum ash slag mass to water in the wet ball milling hydrolysis process is controlled to be 1:1g / ml, and the amount of the solid mixture added is 1% of the mass of the aluminum ash slag; the wet ball milling speed is 150r / min, the medium filling rate is 40%, the medium ratio is: the mass of the zirconium ball with a diameter of 8mm accounts for 30%, the mass of the zirconium ball with a diameter of 10mm accounts for 40%, and the mass of the zirconium ball with a diameter of 12mm accounts for 30%, the ball milling hydrolysis temperature is 100℃, and the ball milling hydrolysis time is 4h. After the wet ball milling hydrolysis, the material is filtered and dried to obtain the detoxified aluminum ash slag. After testing, the nitrogen removal rate is 97.61%, the salt removal rate is 97.43%, and the fluorine solidification rate is 95.85%.

[0046] Example 5

[0047] Aluminum ash (metal aluminum content 8.9%, Al2O3 content 44.9%, AlN content 20.5%, NaCl / KCl total content 6.1%, fluorine content 2.56%) produced by a recycled aluminum plant was used as raw material; firstly, the aluminum ash slag was added with 4% ball milling aid (calcium chloride: calcium peroxide: sodium peroxide = 1:0.5:0.4) for dry ball milling. After ball milling, the mass of the -800 mesh size of the material accounted for 57.7%, the -400 mesh size accounted for 76.5%, and the -200 mesh size accounted for 95.3%; the obtained ball milled material was added with ammonium bicarbonate: lignin sulfonic acid A solid mixture of calcium: polyethylene glycol (PEG4000) = 1:2:3, water is added at the same time for ball milling hydrolysis, the volume ratio of aluminum ash slag mass to water in the wet ball milling hydrolysis process is controlled to be 1:2g / ml, and the amount of the solid mixture added is 1.5% of the mass of aluminum ash slag; the wet ball milling speed is 100r / min, the medium filling rate is 40%, the medium ratio is: the mass of zirconium balls with a diameter of 8mm accounts for 30%, the mass of zirconium balls with a diameter of 10mm accounts for 40%, and the mass of zirconium balls with a diameter of 12mm accounts for 30%, the ball milling hydrolysis temperature is 80°C, and the ball milling hydrolysis time is 5h. After wet ball milling hydrolysis, the material is filtered and dried to obtain the detoxified aluminum ash slag. After testing, the nitrogen removal rate is 98.56%, the salt removal rate is 97.11%, and the fluorine solidification rate is 99.09%.

Claims

1. A method for deep detoxification of secondary aluminum ash by wet method, characterized in that: Aluminum ash slag and a ball milling aid are dry-milled, the dry-milled material is wet-milled with a reaction inducer and water, and the wet-milled material is filtered and dried; the ball milling aid comprises calcium chloride and calcium peroxide; the reaction inducer comprises ammonium bicarbonate, calcium lignin sulfonate and polyethylene glycol; the mass ratio of polyethylene glycol to ammonium bicarbonate is not greater than 3; the mass of the reaction inducer is 0.5% to 2% of the mass of the aluminum ash slag; the liquid-solid ratio of water to aluminum ash slag is 0.5 to 3 mL: 1 g.

2. The method for deep detoxification of secondary aluminum ash by wet method according to claim 1, characterized in that: The mass ratio of calcium chloride to calcium peroxide in the ball milling aid is 1:0.3-0.

8.

3. The method for deep detoxification of secondary aluminum ash by wet method according to claim 1, characterized in that: The ball milling aid contains sodium peroxide; the mass ratio of the sodium peroxide to calcium chloride is not greater than 0.

5.

4. A method for deep detoxification of secondary aluminum ash by wet method according to any one of claims 1 to 3, characterized in that: The mass of the ball milling aid is 1% to 6% of the mass of the aluminum ash slag.

5. The method for deep detoxification of secondary aluminum ash by wet method according to claim 1, characterized in that: The particle size distribution of the dry ball mill material meets the following requirements: the mass proportion of the -800 mesh particle size is 40% to 60%, the mass proportion of the -400 mesh particle size is 60% to 80%, and the mass proportion of the -200 mesh particle size is not less than 90%.

6. The method for deep detoxification of secondary aluminum ash by wet method according to claim 1, characterized in that: The mass ratio of ammonium bicarbonate to calcium lignin sulfonate in the reaction inducer is 1:1-5.

7. The method for deep detoxification of secondary aluminum ash by wet method according to claim 1, characterized in that: The conditions for wet ball milling are: temperature of 50-100°C, time of 1-5h, ball milling speed of 50-150r / min, ball milling medium volume filling rate of 35%-50%, and ball milling medium ratio: 8mm diameter zirconium ball mass accounts for 25%-35%, 10mm diameter zirconium ball mass accounts for 30%-50%, and 12mm diameter zirconium ball mass accounts for 25%-35%.

8. The method for secondary aluminum ash wet deep detoxification according to claim 1, characterized in that: The filtrate produced by the filtration is returned to the wet ball milling process.

Citation Information

Patent Citations

  • Method of removing nitrogen of aluminum ash and slag

    CN108671462A

  • Reinforced aluminum ash desalting and denitriding method

    CN110314923A

  • Method for efficiently recovering metal aluminum from aluminum ash

    CN113856833A